The Aldo Rossi and John Hejduk’s collections - Bronstein, Laís (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2018)
In an analysis of the proposals and architectural projects from the international debate of the 60s and 70s, it becomes apparent the recurrence in the creation of systems from a defined and limited formal repertoire. Among the architects who are part of this time, we distinguish Aldo Rossi and John Hejduk, whose working mechanisms reveal the existence of a specific and limited formal universe of figures and elements that reappear at every new design. A closely contact between these two architects took place in the mid-70s when Rossi spends a season in the US, and teaches at the Cooper Union in New York, then headed by Hejduk. Rossi makes use of pure geometric shapes and the mechanism of analogy in his sketches and drawings. Hejduk also uses pure geometric forms in building its unusual “structures”, that reappear every new project. The idea of collection, such as building a system, is the interpretive key that allows the approach of these two authors, whose formal worlds appear to be, at first glance, so distinct.